The Effect of Chemomechanical Caries Removal and Different Bonding Systems on Shear Bond Strength of Carious Dentin (In Vitro Study) (Mustansiria Dental Journal, 2018)
The purpose of this in vitro study was to determine whether shear bond strength(SBS) to chemomechanically excavated dentine by Carisolv (CS) differed from theSBS after conventional caries removal by bur (CB), with the use of the followingadhesive systems: [Total-etch (TE), etch and Compobond1, etch, prime and bondingresin]; [Self-etch (SE), Xeno v, one component self-etching dental adhesive] and [Noetch(NE), Compobond1, prime& bond only]. Fifty human molars with occlusal carieswere used to prepare dentin samples which were assigned to 5 groups: group I and IIIthe prepared samples treated by CB and CS respectively then with TE, group II andIV the prepared samples treated by CB and CS respectively then with SE, while ingroup V the prepared samples treated by CS and then with NE. For each sample therewas light cured composite core build up. After water storage, the samples were testedin a single-plane shear test assembly. The results demonstrated that there werestatistical significant differences with in the mode of caries removal groups and alsothere were statistical significant differences between the bonding systems which affectSBS of carious dentin at p < 0.01, with in favor of the TE over SE. The present datademonstrate that with the use of CS on (carious dentin, there was either increase ordecrease in bond strength in relation with different bonding systems.